Income Distribution in Network Markets - Corrado Benassi; Marcella Scrimitore (Economics and Econometrics Research Institute (EERI), 2015)
We enquiry about the effects of first and second order stochastic dominance shifts of the distribution of the consumers' willingness to pay, within the standard model of a market with network externalities and hump-shaped demand curve. This issue is analyzed in the polar cases of perfect competition and monopoly. We find that, while under perfect competition both types of distributional changes result in higher output, provided marginal costs are low enough, in the monopoly case the final outcome depends on the way income distribution and the network externality interact in determining market demand elasticity.
Keywords: D31; D40; L1; 330; Network externalities; income distribution; stochastic dominance